MISKOMUNIKASI DIADIK DENGAN KAUM TULI : Analisis Komunikasi Interpersonal dengan Kaum Tuli - Wahjoe Mawardiningsih; Christina Nur Wijayanti (Universitas Islam Balitar, 2018)
The deafs communicate non-verbally by sign speech. The sign speech that is not understanable by the communicator or the communicant, causes miscommunication. The understanding of the sign speech meaning is needed in order to make a positive interpersonalcommunication and relationship. The aim of the research is to find out interpersonal communication in the understanding of non-verbal communication with sign speech, decrease the conflict that causes miscommunication. The kind of the research is qualitative research with data collecting technique of theparticipant observation, interview, and documentary research. The data analysis implemented is qualitative data analysis with interactive model from Miles and Huberman. The kind of the research is descriptive qualitative research, explains and implements the research model in its real condition, the data used is verbal data. The primary and secondary data are obtained from the result of interview, observation, and literary review. The result of the research shows that the positive interpersonal communication grows positive interpersonal relationship, and grows the confidence for the deafs. The result of the research is based on interpersonal communication, they are: openess, emphaty, supportiveness, positiveness, equality. The result shows the needs more openess, emphaty, supportiveness, and positiveness from the communicator or communicant who are not deaf.